Recent progress of industrial preparation of metal–organic frameworks: synthesis strategies and outlook. (March 2022) - He, Qingqing; Zhan, Feiyang; Wang, Huayu; Xu, Weili; Wang, Haoyu; Chen, Lingyun
Abstract: Metal–organic frameworks (MOFs) are a class of advanced porous crystalline materials with broad application prospects in energy and environmental sustainability fields. They have the advantage of being adjustable in terms of porosity and chemical function,  and controllability of structure and properties required for specific applications. However, at the same time, they possess many defects, such as lack of scalable, environmentally sustainable manufacturing methods, and producing high cost. Those resulting in industrial adoption of MOFs has been slow. At present, albeit some MOFs have been industrialized, there are still some issues to be solved. In addition, for MOFs that have yet reached industrialization, it is still a challenge to transition them from laboratory preparation to industrial production,  so that their development in practical application has not reached the expectation. Therefore, this article reviews the scalable and sustainable manufacturing aspects of MOFs from the following aspects: First, what aspects need to be paid attention to in order to realize industrial production and to what extent has industrialization reached today. Moreover, in the preparation of MOFs materials, what methods have the prospect of scalable and sustainable production and give solutions. Graphical abstract: Image 1 Highlights: A comprehensive and thorough review about industrial preparation of metal–organic framework (MOFs) was given. Various methods for production of MOFs were presented. Advantages and disadvantages of different preparation methods were compared. The future challenges and directions of industrial preparation of MOFs were recommended.